2005
DOI: 10.1073/pnas.0408568102
|View full text |Cite
|
Sign up to set email alerts
|

The fluorescence resonance energy transfer (FRET) gate: A time-resolved study

Abstract: The two-step energy-transfer process in a self-assembled complex comprising a cationic conjugated polymer (CCP) and a dsDNA is investigated by using pump-dump-emission spectroscopy and time-correlated single-photon counting; energy is transferred from the CCP to an ethidium bromide (EB) molecule intercalated into the dsDNA through a fluorescein molecule linked to one terminus of the DNA. Time-dependent anisotropy measurements indicate that the inefficient direct energy transfer from the CCP to the intercalated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
90
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 106 publications
(95 citation statements)
references
References 20 publications
4
90
0
1
Order By: Relevance
“…6B). These phenomena clearly demonstrate dipolar-mediated energy transfer (FRET) between these two fluorophores (Xu et al 2005;Gilmore et al 2011). The intensity of SRB reached the lowest level when DsrA was titrated to ;67% of the Hfq hexamer molar concentration.…”
Section: Structure Evidence Of Ec Hfq Cooperation Genes and Developmentmentioning
confidence: 80%
“…6B). These phenomena clearly demonstrate dipolar-mediated energy transfer (FRET) between these two fluorophores (Xu et al 2005;Gilmore et al 2011). The intensity of SRB reached the lowest level when DsrA was titrated to ;67% of the Hfq hexamer molar concentration.…”
Section: Structure Evidence Of Ec Hfq Cooperation Genes and Developmentmentioning
confidence: 80%
“…Figure 3(a) also shows that under similar conditions, the energy transfer efficiency is much lower with PFN/dsDNA/TO, most likely as a result of orientation mismatch between the transition moment of intercalated TO and the polymer backbone, as previously observed for the case of ethidium bromide. [21] At [RU] ¼ 2 Â 10 À6 M, the PFN-sensitized emission for ssDNA 1 / TO is approximately eight-fold more intense than that observed for PFN/ dsDNA/TO. The better response of PFN to ssDNA 1 /TO could be mainly attributed to the improved orientation between PFN and ssDNA 1 /TO, which is due to the random orientation of TO associated with the flexible ssDNA 1 .…”
Section: Resultsmentioning
confidence: 97%
“…[19] However, a recent FRET study between a CCP and ethidium bromide intercalated into dsDNA showed poor efficiencies. [20,21] Time-dependent anisotropy measurements revealed that the low FRET efficiency was due to a non-optimal (orthogonal) orientation between the transition moment of the optically active polymer backbone and that of ethidium bromide within the dsDNA structure. [22] We anticipated that TO dyes associated with ssDNA would have more geometric freedom to conform to the CCP structure, when compared to dyes intercalated within the more rigid dsDNA.…”
Section: Communicationmentioning
confidence: 99%
“…When this distance is close to Forster critical radius, the energy transfer occurs within femtoseconds [26]. On the other hand, the excited state decay of donor PFP occurs exponentially with an average lifetime of ≈90 ps (≈30 ps in presence of the acceptor) [27]. The electrostatic energy is, therefore, transferred from donor to acceptor before the former can emit its photoluminescence (PL).…”
Section: Introductionmentioning
confidence: 99%